What determines China's housing price dynamics? New evidence from a DSGE-VAR - Chunping Liu; Zhirong Ou (Cardiff University, Cardiff Business School, 2017)
We investigate what determines China's housing price dynamics using a DSGE-VAR estimated with priors allowing for the featured operating of normal and "shadow" banks in China, with data observed between 2001 and 2014. We find that the housing demand shock, which is the essential factor for housing price "bubbles" to happen, accounts for over 80% of the housing price fluctuation. We also find that a prosperous housing market could have led to future economic growth, though quantitatively its marginal impact is small. But this also means that, for policy-makers who wish to stabilise the housing market, the cost on output reduction would be rather limited.
Keywords: C11; E32; E44; R31; 330; Housing price; Bubbles; Market spillovers; DSGE-VAR; China